Determinants of corporate green investment practices in the Johannesburg Stock Exchange (JSE) listed firms - Ganda, Fortune (My University, 2016)
The purpose of this study was to determine the factors which spur corporate green investment practices amongst firms listed on the Johannesburg Stock Exchange (JSE). The data were sourced from companies’ annual sustainability reports over a period of five years (2010 to 2014) and were subjected to content analysis. This quantitative study adopted a multiple case research approach as it examined all 100 South African CDP companies listed on the JSE. Data analysis was conducted using Chi-Square tests, together with Phi and Cramer’s V tests. The findings indicate that legislation influences the corporate green investment practices of JSE listed firms as do corporate image, profitability and environmental consciousness. Legislation, corporate image, profitability and environmental consciousness showed a significant relationship with the green investment practices of JSE listed firms. Furthermore, the number of JSE listed firms which supported each of these variables as a factor which promoted firm green investment practices steadily increased during the period 2010 to 2014. This study makes a modest contribution to knowledge by suggesting a framework to understand corporate green investment practice in JSE listed firms based on the study’s findings and a review of the literature. Arising from this framework, suggestions are made for further research to scrutinise how a combination of the four determinants of firm green investment practice could influence corporate eco-efficiency, firms’ engagement in green operations and markets, corporate environmental compliance and the incorporation of environmental performance measures in corporate performance measurement systems. KEY CONCEPTS: Environmental legislation; Corporate image; Profitability; Environmental consciousness; Green investment practices;Environmental legislation JSE listed firms.
Thesis (Ph. D. Commerce (Accounting)) -- University of Limpopo, 2016
Keywords: Environmental legislation; Corporate image; Green investment practices; Corporations -- South Africa; Environmental protection; Climatic changes; Investment analysis